Encylopedia of Indian philosophies Volume II Indian metaphysics and epistemology The tradition of Nyaya-Vaisesika before Gangesa - Potter,Karl.H (Delhi Motilal Banarsidas, 2009)
Introduction to the philosophy of Nyaya-vaisesika